Indirekte Schätzung des Fahrbahnnässegrads zur Detektion von gefährlichen Fahrzuständen - Schmiedel, Bernhard (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2023)
An estimation of the road wetness level supports the driver as well as the vehicle to maneuver safely. This study presents the fundamentals of a system that uses structure-borne sound measurements at various positions on the vehicle to detect the water spraying up from the tires and uses this information to estimate the degree of road wetness. The system finds its first application in the Porsche 911, Type 992.